MIDWIFERY CARE MANAGEMENT FOR A 12-YEAR-OLD PANT WITH POST-OP PENOSCROTOL HYPOSPADIA IN THE MUSDALIFAH WARD MEDAN HAJI HOSPITAL IN 2025 - Umroh, Arfadilla; Isabela Amandine Br Siregar; Riszanaya Mukti; Alvin Adelia Cahyaningtyas; Ariska Fauzianty (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Hypospadias is one of the most common congenital abnormalities in male children and requires surgical management. Postoperative conditions often lead to problems such as pain and risk of infection, thus requiring comprehensive midwifery care to support patient recovery. At RSU Haji Medan, cases of hypospadias in children are still found and require optimal follow-up care. Objective: This study aims to describe the implementation of midwifery care in children with post-operative penoscrotal hypospadias in managing pain and preventing complications. Methods: This study used a descriptive case study design with a subject of An. P, a 12-year-old male with post-operative penoscrotal hypospadias. Data were collected through anamnesis, observation, physical examination, and medical record documentation. Results: The assessment results showed that the patient experienced acute pain with a pain scale of 6 after surgery and had a risk of infection. Interventions provided included pain management, wound care, monitoring of vital signs, and education for the patient and family. After continuous care was provided, the pain scale decreased from 6 to 0 within a few days of treatment, and no signs of infection were found in the surgical wound. Conclusion: Comprehensive and continuous midwifery care is effective in reducing pain, preventing complications, and supporting the healing process in patients with post-operative hypospadias.